Validation and Verification of Smart Contracts: A Research Agenda. - Magazzeni, Daniele; McBurney, Peter; Nash, William (Computer (00189162), 2017)
Smart contracts might encode legal contracts written in natural language to represent the contracting parties’ shared understandings and intentions. The issues and research challenges involved in the validation and verification of smart contracts, particularly those running over blockchains and distributed ledgers, are explored.